Aac in india : the current status of art - Balaraju C (Journal of All India Institute of Speech and Hearing, 1970)
A survey was designed to gather information about the current status of AAC in India. Specific information about which schools/centers were usingAAC systems, why they were using them, with which type of children and with what success in India, was obtained. For the study a total of 184 questionnaires were sent to different schools for the mentally handicapped, cerebral palsied and autism throughout India. The responses obtained were 30.5%.